BIOMEDICINAL AND GASTROPROTECTIVE ASPECTS OF ORGANOBISMUTH COMPOUNDS: RECENT APPROACHES AND FUTURE PERSPECTIVES - SYED MISBAHUL HASAN; SHIVBHADRA SINGH; RAVI KANT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Peptic ulcer is a disease caused due to an imbalance of aggressive and defensive factors in the body. Helicobacter pylori infections and colonization are also associated strongly to the peptic ulcer disease. Bismuth-containing organic compounds have been attributed to a major influential role in the successful treatment of peptic ulcer by inhibiting gastric acid secretion and provide cytoprotective properties which result in ulcer healing. Hence, the objective of this review is to discuss recent approaches and future perspectives of organobismuth compounds in the treatment of peptic ulcer. Results: A total of 112 papers were included in the review, among them 20 papers describe the pathophysiology of peptic ulcer, 10 papers discuss about diagnostic test for H pylori infection, 4 papers describe the drug regimen used in peptic ulcer treatment, 13 papers discuss about failure and alternative therapies for treatment of peptic ulcer, 8 papers describe the chemistry of bismuth, 20 papers discuss about mechanism of action of bismuth, 27 papers describe the newer bismuth complexes for H. pylori eradication, and 8 paper discuss about gastroprotective activity of bismuth-containing derivatives. Conclusion: Organobismuth compounds/drugs are effective to eradicate H. pylori in conjunction with antibiotics. It also provides gastroprotective action and dramatic decrease of relapse rate which accounts for further exploration of organobismuth compounds to pave new ways for the design and synthesis of novel compounds in the effective treatment of peptic ulcer.